2021
DOI: 10.3389/fphar.2021.729220
|View full text |Cite
|
Sign up to set email alerts
|

Kratom Use Within the Context of the Evolving Opioid Crisis and the COVID-19 Pandemic in the United States

Abstract: Kratom (Mitragyna speciosa, Korth.) is an evergreen tree that is indigenous to Southeast Asia. When ingested, kratom leaves or decoctions from the leaves have been reported to produce complex stimulant and opioid-like effects. For generations, native populations in Southeast Asia have used kratom products to stave off fatigue, improve mood, alleviate pain and manage symptoms of opioid withdrawal. Despite the long history of kratom use in Asia, it is only within the past 10–20 years that kratom has emerged as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 76 publications
0
11
0
1
Order By: Relevance
“…More and better research, including wellcontrolled, prospective studies, is necessary to further elucidate kratom's potential for good and harm and the moderators of its effects" (Swogger and Walsh, 2018). The therapeutic potential of kratom based on surveys, anecdotal reports, and nonclinical research supports the plausibility of such benefits as discussed by other reviewers (Prozialeck et al, 2019;Hemby et al, 2019;Yue et al, 2018;Grundmann et al, 2018;Kruegel and Grundmann, 2018;Sharma and McCurdy, 2021;Swogger et al, 2018;Prozialeck et al, 2021).…”
Section: Public Health and Individual Benefits Of Kratommentioning
confidence: 91%
“…More and better research, including wellcontrolled, prospective studies, is necessary to further elucidate kratom's potential for good and harm and the moderators of its effects" (Swogger and Walsh, 2018). The therapeutic potential of kratom based on surveys, anecdotal reports, and nonclinical research supports the plausibility of such benefits as discussed by other reviewers (Prozialeck et al, 2019;Hemby et al, 2019;Yue et al, 2018;Grundmann et al, 2018;Kruegel and Grundmann, 2018;Sharma and McCurdy, 2021;Swogger et al, 2018;Prozialeck et al, 2021).…”
Section: Public Health and Individual Benefits Of Kratommentioning
confidence: 91%
“…There is recreational use; however, many people who use opioids recreationally report kratom as a poor substitute for producing opioid-like euphoria but do find it useful to self-manage withdrawal and discontinue opioid use (Coe et al 2019;Garcia-Romeu et al 2020;Prozialeck et al 2019;Swogger et al 2022). Estimates of incidence and prevalence of intake vary from 2 to 16 million in the United States (US) (American Kratom Association 2019; Covvey et al 2020;Henningfield et al 2021;Palamar 2021;Schimmel et al 2021) and many millions more globally, with the highest prevalence in Southeast Asia and Indonesia where kratom grows in abundance and has been widely consumed for centuries (Brown et al 2017;Cinosi et al 2015;Prozialeck et al 2021;WHO ECDD 2021;Vicknasingam et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In October 2021, the US Department of Health and Human Services (US DHHS) announced that drug overdose prevention efforts would include a substantial increase in harm reduction efforts to reduce opioid and other drug overdose deaths (US DHHS 2021). Kratom was not mentioned in the 2021 US DHHS announcement; however, US national surveys indicated that kratom is increasingly taken as a harm reduction strategy by thousands of opioid users to reduce and/or eliminate their opioid use related to pain and/ or opioid use disorder (Grundmann 2017;Grundmann et al 2018;Coe et al 2019;Garcia-Romeu et al 2020;Prozialeck et al 2019Prozialeck et al , 2020Prozialeck et al , 2021Swogger et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Kratom ( Mitragyna speciosa ), a native plant in Southeast Asia, 1 has received public, scientific, and political attention in recent years. 2 - 4 In 2021, the World Health Organization (WHO) Expert Committee on Drug Dependence (ECDD) decided against recommending a critical review of kratom, electing instead to continue surveillance of this herb. 5 Although the United States (U.S.) Food and Drug Administration (FDA) does not report any FDA-approved uses for kratom, 6 the National Institute on Drug Abuse (NIDA) is funding numerous projects related to kratom and its alkaloids.…”
Section: Introductionmentioning
confidence: 99%